Factors associated with Food Safety Practices (FSP) among visitors in the Depok Beach Area in Yogyakarta, Indonesia - Suryani, Dyah; Rustiawan, Asep; Jannah, Arihni Arihatal (Public Health of Indonesia, 2023)
Background: The availability of safe, healthy, and clean food in tourism places is essential to ensure customers’ satisfaction. Most previous studies focused on food safety practices among food handlers. However, personal food safety practices are needed to prevent foodborne diseases. Objective: This study aimed to identify the factors associated with food safety practices among people who visited Depok Beach. Methods: A quantitative approach was done on 211 Depok Beach visitors selected by the accidental sample method. This study was conducted from September to October 2022. Descriptive statistics, chi-square, and binary logistic regression were used for data analysis. Results: This study found that factors such as marital status, knowledge, and attitude were 2.8, 1.2, and 2.2 times, respectively, more likely to practice poor food safety practices.  Conclusion: The food safety practice among visitors was less than average. The factors associated with food safety practices among visitors were marital status, knowledge, and attitude about food safety. Health promotion about food safety for customers is needed. Further studies could mix with the qualitative approach to get comprehensive findings.